2022
DOI: 10.1007/s13668-022-00427-y
|View full text |Cite
|
Sign up to set email alerts
|

Improving Iodine Status in Lactating Women: What Works?

Abstract: Purpose of Review Iodine deficiency is a global concern, and in recent years, there has been a significant improvement in the number of countries identified as being iodine-sufficient. This review considers the best strategies to ensure iodine sufficiency among breastfeeding women and their infants. Recent Findings Fortification strategies to improve iodine intake have been adequate for school-age children (SAC); however, often, iodine deficiency remains f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…The median UIC cut-off to determine iodine sufficiency in lactating women is 100 µg/l, which is lower than pregnant women because in lactating women, ingested iodine is excreted both in urine and breast milk (5) . Therefore, due to the variation in the partition of iodine between breast milk and urine, both BMIC and UIC are recommended to be included when assessing iodine status in breast-feeding women (4) . On the other hand, the median UIC cut-off value for classifying iodine sufficiency during pregnancy is 150 μg/l, which was established on the basis of an average daily urine volume of 1·5 l (5) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The median UIC cut-off to determine iodine sufficiency in lactating women is 100 µg/l, which is lower than pregnant women because in lactating women, ingested iodine is excreted both in urine and breast milk (5) . Therefore, due to the variation in the partition of iodine between breast milk and urine, both BMIC and UIC are recommended to be included when assessing iodine status in breast-feeding women (4) . On the other hand, the median UIC cut-off value for classifying iodine sufficiency during pregnancy is 150 μg/l, which was established on the basis of an average daily urine volume of 1·5 l (5) .…”
Section: Discussionmentioning
confidence: 99%
“…This is because the iodine content in breast milk is influenced by the mother's iodine intake and overall iodine status (4) . In addition, BMIC is independent of maternal fluid intake (4) . A recent systematic literature review has suggested that there have been inconsistencies in the relationship between BMIC and UIC in lactating women, which may be due to the differences in lactation stages, maternal iodine status and sampling collection time (11) .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Daily supplementation with iodine is not an ideal strategy to overcome deficiency. [2] Hypothesis The development of technology for enriching bakery products with iodine will solve the problem of iodine deficiency conditions of the population, ensuring the intake of iodine into the human body with food.…”
Section: Introductionmentioning
confidence: 99%
“…9 However, both inadequate and excessive I intake can have adverse effects on thyroid health. 10 In general, the consumption of seafood is not high in geographic areas distant from the sea; furthermore, for agricultural products, the I content depends on the concentrations found in the soil and/or irrigation water. 11 Potassium plays a significant role in maintaining overall health, but it requires careful attention in the context of chronic kidney disease (CKD).…”
Section: Introductionmentioning
confidence: 99%